2007
DOI: 10.1007/s12247-007-9004-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Terahertz Pulse Imaging and Near-Infrared Spectroscopy for Rapid, Non-Destructive Analysis of Tablet Coating Thickness and Uniformity

Abstract: In this study, coating thickness and uniformity of production-scale pharmaceutical tablets were investigated using near-infrared (NIR) and terahertz pulse imaging (TPI) spectroscopy. Two coating formulations were considered; samples for each coating formulation were obtained at 0, 1, 2, 3, 4, and 5% coating weight. NIR spectra were collected, and regressed with respect to batch percent weight gain. While standard errors of calibration (SEC) less than 0.5% were observed for both formulations, the calibrations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Terahertz Pulsed Imaging (TPI) was described as a powerful alternative for coating thickness determination due to its non-destructive nature and its ability to provide a three dimension map of coating thickness over the whole tablet surface (Fitzgerald et al, 2005;Ho et al, 2007;Zeitler et al, 2007). Some authors concluded that this method could only be applied to the monitoring of thickness values higher than 35 lm due to the detection limit of the instrument (Cogdill et al, 2007;Maurer and Leuenberger, 2009). For the present study, since specifications for dissolution rate requires high polymer deposits (Siepmann et al, 2007), TPI could be selected as a relevant reference method.…”
Section: Introductionmentioning
confidence: 99%
“…Terahertz Pulsed Imaging (TPI) was described as a powerful alternative for coating thickness determination due to its non-destructive nature and its ability to provide a three dimension map of coating thickness over the whole tablet surface (Fitzgerald et al, 2005;Ho et al, 2007;Zeitler et al, 2007). Some authors concluded that this method could only be applied to the monitoring of thickness values higher than 35 lm due to the detection limit of the instrument (Cogdill et al, 2007;Maurer and Leuenberger, 2009). For the present study, since specifications for dissolution rate requires high polymer deposits (Siepmann et al, 2007), TPI could be selected as a relevant reference method.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral resolution is limited by the wavelength of terahertz radiation, for example 150 and 400 µm at 1 and 2.7 THz, respectively [10,13], and the depth resolution is limited by the terahertz pulse duration of <200 fs. The achievable lateral resolution for pharmaceutical tablets is typically between 150-250 µm, at approximately 1.5 to 2.7 THz frequency range, and 30-40 µm for the depth resolution [6,7,10,14,15]. Investigations on improving spatial resolution of a THz-TDS system have been presented elsewhere [16][17][18].…”
Section: Coating Thickness Analysismentioning
confidence: 99%
“…The ability of TPI to measure the absolute coating thickness has made it an attractive reference method for comparison and calibration against various PAT. For example, it has been compared against the well-established NIR spectroscopy for coating thickness and uniformity of production-scale pharmaceutical dosage forms [14]. Comparing the two techniques, NIR spectroscopy is an indirect measurement, where coating thickness needs to be correlated with the absorbance that in turn requires multivariate calibration using partial least squares (PLS) for quantitative analysis.…”
Section: Comparison and Calibration Of Patmentioning
confidence: 99%
“…The system has been described in detail by Zeitler et al 20 The precision and reproducibility have been studied in detail. [22][23][24] The reflected time-offlight radiation is analyzed in the time domain to measure the thickness of the tablet coating at points nominally 250 mm apart over the surface. Reflections occurs whenever there is a change in refractive index.…”
Section: Terahertz Pulsed Imagingmentioning
confidence: 99%